2023
DOI: 10.3390/antibiotics12020250
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Plans to Optimize Antimicrobial Use in the Pediatric Population in Catalan Hospitals: The VINCat Pediatric PROA SHARP Survey

Abstract: In Spain, many programs have been introduced in recent years to optimize antimicrobial stewardship in pediatric care (known as pediatric PROA). However, information on the current situation of these programs is scarce. The present study assesses current antimicrobial use in pediatric care in the hospitals of Catalonia affiliated with the VINCat pediatric PROA group. Between December 2020 and January 2021, an electronic survey related to the design and use of PROA was administered to members of PROA teams in ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…This survey revealed that while most hospitals have implemented measures suggested by pediatric ASPs, many have not established their own dedicated program. It is crucial to provide these programs with more resources so that these hospitals can create tailored initiatives and define specific indicators for this age group [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This survey revealed that while most hospitals have implemented measures suggested by pediatric ASPs, many have not established their own dedicated program. It is crucial to provide these programs with more resources so that these hospitals can create tailored initiatives and define specific indicators for this age group [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The term "stewardship" refers to the careful and responsible use of something relied upon for one's health, such as natural resources [59]. To curb antimicrobial resistance, every physician must know how to use antibiotics by prescribing them appropriately and educating their patients and colleagues on the proper use of this basic but increasingly limited medical resource [158][159][160][161].…”
Section: Food Chainmentioning
confidence: 99%
“…Programs for optimizing the use of antibiotics (PROAs) have been recently developed to prevent or reduce the emergence of antimicrobial resistance; to optimize the selection, dose, and duration of antibiotic treatments; and to reduced adverse effects [20]. However, these programs have been mostly implemented in adults and in the hospital setting, although some of them targeted outpatient pediatric populations attended in primary care [21][22][23].…”
Section: Introductionmentioning
confidence: 99%